Модель функціонування цифрової ідентичності та засоби її втілення - Гаража, Р. Ю. (ХНУРЕ, 2023)
This work is devoted to the research of the digital identity model and the identification of means capable of ensuring its functioning in accordance with the specified requirements. The main requirements for the implementation of digital identity are its privacy and the flexibility of its expansion. Flexibility can be achieved through the use of a three-participant identity model. Such participants are the owner of the identity, the postulator of the statements about the owner, and the verifier. Privacy is achieved by using zero-knowledge proofs. The resulting system allows participants to edit, verify and submit digital identity instances for verification using the unified identity standard and protocols.